Asidhāra - Muraḷīkṛṣṇa, Kastūri (Kastūri Pracuraṇalu, 2004)
A novel, based on educational theme; previously serielized in Jagruti, a Telugu magazine
Telugu in Telugu-Schr
Keywords: Telugu-Sprache; Kurzroman; Geschichte 1900-2000